2006
DOI: 10.1182/blood-2006-04-017780
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1/2 randomized, placebo-control trial of palifermin to prevent graft-versus-host disease (GVHD) after allogeneic hematopoietic stem cell transplantation (HSCT)

Abstract: Palifermin, a recombinant human keratinocyte growth factor, was tested for potential benefits on acute graft-versus-host disease (GVHD) and hematopoietic recovery in allogeneic hematopoietic stem cell transplantation (HSCT) recipients. This randomized, double-blind, placebocontrolled, dose-escalation study assessed the safety and tolerability of palifermin (n ‫؍‬ 69) as compared with placebo (n ‫؍‬ 31) in patients conditioned with cyclophosphamide and fractionated total-body irradiation (Cy/TBI) or busulfan an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
109
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(124 citation statements)
references
References 34 publications
(25 reference statements)
11
109
4
Order By: Relevance
“…None showed an impact on the occurrence of acute GVHD [28,35,37] or chronic GVHD [90]. The impact on mucositis was not consistent, with one study showing a decrease of oral mucositis only in patients conditioned with cyclophosphamide and TBI, but not in patients receiving a less mucotoxic regimen of busulfan and cyclophosphamide [35]. These findings are in line with a retrospective study on 251 patients published after the cut-off date for this review [91].…”
Section: Discussion and Late Breaking Reportssupporting
confidence: 75%
See 2 more Smart Citations
“…None showed an impact on the occurrence of acute GVHD [28,35,37] or chronic GVHD [90]. The impact on mucositis was not consistent, with one study showing a decrease of oral mucositis only in patients conditioned with cyclophosphamide and TBI, but not in patients receiving a less mucotoxic regimen of busulfan and cyclophosphamide [35]. These findings are in line with a retrospective study on 251 patients published after the cut-off date for this review [91].…”
Section: Discussion and Late Breaking Reportssupporting
confidence: 75%
“…The question whether palifermin reduces GVHD has been addressed in a number of clinical trials of allogeneic HSCT following myeloablative conditioning using cyclophosphamide plus TBI or CT only. None showed an impact on the occurrence of acute GVHD [28,35,37] or chronic GVHD [90]. The impact on mucositis was not consistent, with one study showing a decrease of oral mucositis only in patients conditioned with cyclophosphamide and TBI, but not in patients receiving a less mucotoxic regimen of busulfan and cyclophosphamide [35].…”
Section: Discussion and Late Breaking Reportsmentioning
confidence: 96%
See 1 more Smart Citation
“…Palifermin was associated with reduced incidence and severity of mucositis (measured three times weekly), but only in patients conditioned with fractionated TBI-based regimens. 12 Levine et al 13 reported on the long-term outcomes of this cohort and found no difference between the palifermin and placebo groups in the incidence of chronic GVHD or relapse risk. As shown in some of the prior trials, 11,12 there was no positive impact of palifermin on either grade 2 --4 or grade 3 --4 acute GVHD incidence or severity.…”
Section: Discussionmentioning
confidence: 99%
“…10 However, another retrospective cohort study showed no effect of palifermin on GVHD in allo-SCT. 11 In a prospective, randomized trial, Blazar et al 12 investigated various dosing regimens of palifermin in allo-SCT and concluded there were no significant differences in acute GVHD incidence, acute GVHD severity, survival or day 100 relapse rates between the palifermin and placebo groups. Palifermin was associated with reduced incidence and severity of mucositis (measured three times weekly), but only in patients conditioned with fractionated TBI-based regimens.…”
Section: Discussionmentioning
confidence: 99%